Math

rewrite the expression in terms of the first power of cosine.
cos^3(x)sin^4(x)

  1. 👍 0
  2. 👎 0
  3. 👁 118

Respond to this Question

First Name

Your Response

Similar Questions

  1. Calculus 12th grade (double check my work please)

    1.)Find dy/dx when y= Ln (sinh 2x) my answer >> 2coth 2x. 2.)Find dy/dx when sinh 3y=cos 2x A.-2 sin 2x B.-2 sin 2x / sinh 3y C.-2/3tan (2x/3y) D.-2sin2x / 3 cosh 3yz...>> my answer. 2).Find the derivative of y=cos(x^2) with

  2. Math

    Rewrite the expression in terms of the first power of the cosine sin^8(x) how do i do this plz help !!

  3. MATHS - URGENT

    Write the expression in terms of sine only. 8(sin 2x − cos 2x)

  4. self-study calculus

    Sketch the curve with the given vector equation. Indicate with an arrow the direction in which t increases. r(t)=cos(t)I -cos(t)j+sin(t)k I don't know what to do. I let x=cos(t), y=-cos(t) and z= sin(t). Should I let t be any

  1. Pre-Calc

    I am really struggling with how to do these problems, I posted them a few minutes ago but the answers/work shown was incorrect. 1) a) Use an Addition or Subtraction Formula to write the expression as a trigonometric function of

  2. calculus/Trig

    Suppose you wish to express sin(3t) in terms of sint and cost. Apply the sum formula to sin(3t) = sin(t+2t) to obtain an expression that contains sin(2t)=sin(t+t) and cos(2t)=cos(t+t). Apply the sum formulas to those two

  3. tigonometry

    expres the following as sums and differences of sines or cosines cos8t * sin2t sin(a+b) = sin(a)cos(b) + cos(a)sin(b) replacing by by -b and using that cos(-b)= cos(b) sin(-b)= -sin(b) gives: sin(a-b) = sin(a)cos(b) - cos(a)sin(b)

  4. trig

    The expression 4 sin x cos x is equivalent to which of the following? (Note: sin (x+y) = sin x cos y + cos x sin y) F. 2 sin 2x G. 2 cos 2x H. 2 sin 4x J. 8 sin 2x K. 8 cos 2x Can someone please explain how to do this problem to

  1. Trig

    Find sin(s+t) and (s-t) if cos(s)= 1/5 and sin(t) = 3/5 and s and t are in quadrant 1. =Sin(s)cos(t) + Cos(s)Sin(t) =Sin(1/5)Cos(3/5) + Cos(-1/5)Sin(3/5) = 0.389418 Sin(s-t) =sin(s)cos(t) - cos(s)sin(t) =sin(-3/5)cos(1/5) -

  2. math

    Simplify and write the trigonometric expression in terms of sine and cosine: sin x +(cot x)(cos x) = 1/f(x) f(x)= ?

  3. Pre Calculus

    Multiply; then use fundamental identities to simplify the expression below and determine which of the following is not equivalent. (sin x + cos x) ^2 a. 1+2sinxcosx b. sec^2x−tan^2x+2cosxsinx c.sec x + 2 sin x/sec x d.

  4. Pre-Calculus

    Write the following expression as the sine, cosine or tangent of an angle. cos 3x cos 2y + sin 3x sin 2y

You can view more similar questions or ask a new question.